A comparative investigation into cold-start and hot-start operation of diesel engine performance with oxygenated fuels during transient and steady-state operation. (15th September 2018) - Zare, Ali; Bodisco, Timothy A.; Nabi, Md Nurun; Hossain, Farhad M.; Ristovski, Zoran D.; Brown, Richard J.
Highlights: Custom test was designed to study the engine performance during cold-start. Oxygenated fuels had higher indicated torque during hot-start transient modes. Oxygenated fuels had lower indicated torque during cold-start transient modes. Oxygenated fuels had higher max in-cylinder pressure at hot-start transient modes. Oxygenated fuels had lower max in-cylinder pressure at cold-start transient modes. Abstract: Using a six-cylinder turbocharged common rail compression ignition engine, this study investigated the effect of oxygenated fuels on transient and steady-state performance. This paper considers the effect of oxygenated fuels on both cold- and hot-start operation. A range of fuel oxygen contents between 0% and 13.57% was derived from diesel, waste cooking biodiesel and two other blends, containing triacetin as a fuel additive. A custom test was designed to investigate engine performance parameters using acceleration, load increase and steady-state modes of operation. For each fuel, the cold-start test was conducted after an overnight engine-off time. In this study, different parameters related to engine performance were studied, such as engine coolant and lubricant temperatures and their rise rate, boost pressure, injected fuel, turbocharger lag, engine speed and torque, start of injection, maximum in-cylinder pressure, maximum rate of pressure rise, cyclic variability, FMEP, mechanical and thermal efficiencies, and BSFC. In comparison with hot-start, the cold-start results indicated a higher injected fuel, indicated torque, maximum in-cylinder pressure, maximum rate of pressure rise, FMEP, BSFC and CoV of IMEP, and a lower SOI, ME and BTE. During cold-start, using oxygenated fuels, instead of diesel, resulted in a lower rate of lubricant temperature rise and a higher BSFC, while decreasing the FMEP. Using oxygenated fuels, instead of diesel, during the idle and transient modes resulted in lower indicated torque and maximum in-cylinder pressure under cold-start whilst, under hot-start, it resulted in higher indicated torque and maximum in-cylinder pressure, because during hot-start, the fuel oxygen is significantly influential in torque build-up during turbocharger lag. While, during cold-start there are some other influential factors. In addition, oxygenated fuels—compared to diesel—experienced higher CoV of IMEP during cold-start while, during hot-start, they had lower values.